Co-production of 1, 4-pentanediol and adipic acid from corn stover with biomass-derived co-solvent: Process synthesis and analysis. (20th July 2022) - Oh, Min-Young; Jin, Gyuhyung; Lee, Bomsock; Kim, Jiyong; Won, Wangyun
Abstract: As environmental issues caused by the use of fossil-derived chemicals arise, efforts to replace fossil-based feedstocks with renewable and environment-friendly resources to mitigate the environmental impact of chemical production have been continuously made. In this study, an integrated process utilizing separation and catalytic conversion was designed to co-produce adipic acid (ADA), a precursor used to produce nylon 6.6, and 1, 4-pentanediol (1, 4-PDO), a monomer for biodegradable polymer, from corn stover as a renewable resource. Cellulose and hemicellulose are simultaneously converted into gamma-valerolactone (GVL), and the GVL is further split and converted into ADA and 1, 4-PDO. The energy consumption for the process is significantly reduced by designing and incorporating a heat exchanger network. Techno-economic analysis and life cycle assessment were performed to evaluate the economic and environmental impacts of the three representative cases having different GVL split ratios for ADA and 1, 4-PDO production. The results indicate that the case producing the most ADA leads to an optimal minimum selling price of 1382/ton ADA under the proposed assumptions and has a marginal impact on the environment compared to the fossil-based ADA production. Uncertainty analysis showed that this co-production process has economic stability against variable market conditions. These results suggest directions to improve the economic and environmental feasibility of the proposed process. Highlights: The co-production process of biochemical monomers from corn stover is developed. Economic feasibility is analyzed through techno-economic analysis. Environmental sustainability is investigated via life-cycle assessment. Sensitivity and uncertainty analyses identify the major cost drivers of the process.